Through the Looking Glass, Darkly: Perceptions of Hate in Interpersonal Relationships. (2015) - Aumer, Katherine; Bahn, Anne Cathrine Krebs; Harris, Sean
Abstract : Current research has focused primarily on how hate works in groups or its theoretical nature. This study replicates previous findings (Aumer-Ryan & Hatfield, 2007 ) that hate is primarily felt towards intimate others or people we spend considerable time with. Ninety-eight participants filled out a survey concerning themselves, the people they love and the people they hate. Participants also filled out a survey about motivations concerning the people they love and hate. Results demonstrate that participants saw people they hate considerably differently than those they love, and themselves. Additionally, this study provides empirical evidence that hate can be used as a predictor of motivation. Specifically, disgust and devaluation were important predictors in negative and positive motivation. Additional studies examining interpersonal hate can help better understand how hate operates and inform current theoretical literature.